Dynamic strength testing of perforated steel - GRP double lap joints - Brambleby,RJ; Louca,LA; Mouring,SE (2014)
Joints between metals and composites are being employed in a range of applications, but the performance of such joints under dynamic loading is not well documented. This paper presents some initial results investigating the tensile strength of steel to GRP double lap joints comparing pseudo static strength with dynamic strength and comparing joints that have non-perforated steel plates with joints that have perforated steel plates. The effect of an intentional manufacturing flaw is also considered. It has been observed that the strength enhancement provided by the perforations is significant, but marginally lower under dynamic loading than under static loading.